Students’ Engagement on Teachers’ Online Feedback with Timing in Study-From-Home Through Learning Management System - Rahma Amalia Aslam; Khoirul Anwar; Nirwanto Maruf (Fakultas Keguruan dan Ilmu Pendidikan - Universitas Gresik, 2022)
This study aimed to investigate students’ engagement with teachers’ online feedback with timing in studyfrom - home through a Learning Management System (LMS). Data were collected from 38 students of SMA Muhammadiyah 1 Gresik who were chosen as a sample in this study. They filled 14 items in questionnaire of students’ engagement which are divided into 4 dimensions: emotional, behavioral, cognitive, and affective engagement. The results showed an average mean score of 3.71, 3.76, 3.87, and 3.97 respectively for emotional, behavioral, cognitive and affective engagement. The results also showed that students generally had a positive experience with the timing of direct and indirect feedback provide by their teachers, with an average mean score of 3.56 and 3.53 respectively. The results indicate that providing timely online feedback to students through an LMS can have a positive impact on stuents’ engagement and performance. The study also has some limitation, such as being conducted in only one school and in one subject area, thus future research should explore these findings in different contexts and subject areas. The results of this study provide a starting point for further research on the topic and can be used to guide future studies on students’ engagement with online feedback with timing in study-from-home through LMS.